Analisis Penggunaan Aplikasi Linkaja Dengan Technology Acceptance Model Pada Grapari Telkom Group Medan Sumatera Utara - Erina Novelia; Ihsan Effendi; Yuni Syahputri (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2021)
The purpose of this study was to determine the effect of Intention to Use  and Perceived Usefulness on Actual System Use through Intention to Use  as an intervening variable in the LinkAja application in GraPARI Telkom Group Medan.The population in this study were all consumers average in one day, amounting to 150 people using a sample of 30 people. Based on the results of the t test (partial) the variable Perceived Ease of Use obtained tcount 4.748 t table 2.048 and significant 0.000 0.05, then Ha is accepted and H0 is rejected, which states that Perceived Ease of Use has a significant effect partially on Perceived Usefulness. The variable Perceived Ease of Use is obtained tcount 4.433 t table 2.051 and significant 0.049 0.05, then Ha is accepted and H0 is rejected, which states that Perceived Ease of Use has a significant effect partially on Intention to Use . The Perceived Usefulness variable is obtained tcount 5,089 ttable 2,051 and significant 0,046 0,05, then ha is accepted and h0 is rejected, which states that Perceived Usefulness has a partially significant effect on Intention to Use . The Intention to Use  variable was obtained tcount 3.140 t table 2.055 and significant 0.040 0.05, then Ha was accepted and H0 was rejected, which stated Intention to Use  partially significant effect on Actual System Use.Based on the intervening test, the results show that Perceived Ease of Use has a correlation with Intention to Use as an intervening variable because it has a value of Pvalue α, namely 0.105 0.05. The Perceived Usefulness variable has a value of 0.264 0.05, which means that it has a positive regression coefficient direction.